Who can stand before a holy God? Literary artistry and theological imagination in the Ark Narrative - Mǎcelaru, Marcel Valentin (Array, 2019)
This article advocates for an interpretation of biblical stories that takes into account their nature and the way in which they are told. The argument begins with observing the predicament of the biblical interpreter in using contemporary historical and/or literary methods to interpret an ancient text expected to convey a theological message. It then offers a close reading of the Ark Narrative (1 Sam 4:1b–7:1) which exemplifies how theological conclusions can be drawn on the basis of the story alone once its literary structure and dramatic development are identified.